Avaliaç\~ao da evoluç\~ao da eficiência e da produtividade em transplantes de órg\~aos no Brasil - Alexandre Marinho (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– Brazil has one of the most extensive public program for organ transplantation in the world, and the Brazilian National Health System (SUS) provides full coverage procedures related to organ donation, transplants, and post-transplant. Despite the relevance of the subject and the existence of long waiting lines, transplantation process efficiency and productivity assessments are still uncommon in Brazil. This study aims to evaluate the efficiency and productivity of the Brazilian states and the Federal District in transforming potential organ donors into actual donations. We applied Data Envelopment Analysis (DEA) and the Malmquist Index in conjunction with the Bootstrap technique, using organ transplantation data from 2013-2021.
Keywords: C14; C61; D61; I18; 330; organ transplantation; efficiency; productivity; Data Envelopment Analysis; Malmquist Index; Bootstrap; Sistema Nacional de Transplantes